2005
DOI: 10.1182/blood-2004-04-1453
|View full text |Cite
|
Sign up to set email alerts
|

Impaired T- and B-cell development in Tcl1-deficient mice

Abstract: IntroductionT-cell prolymphocytic leukemias (T-PLLs) in humans often have chromosomal translocations that juxtapose the T-cell receptor (TCR) ␣/␦ or ␤ locus to the proximity of the T-cell leukemia/ lymphoma-1 gene (TCL1) located in the 14q32.1 region or, less frequently, to lay near its mature T-cell proliferation 1 (MTCP1) gene homolog in the Xq23 region. [1][2][3][4] The ensuing aberrant influence of a TCR enhancer element results in overexpression of the TCL1 or MTCP1 genes. 5,6 Overexpression of either TCL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 43 publications
(68 reference statements)
2
32
0
1
Order By: Relevance
“…Tcl1 À/À mice develop alopecia and skin impairment: macroscopical and histopathological analysis Tcl1 À/À mice show no gross histological or physical abnormality at birth, except a fertility defect and a mild impairment of the immune system in adult life (Kang et al, 2005;Narducci et al, 1997aNarducci et al, , b, 2002. These mice develop a form of mild alopecia starting from the head and neck region (Figure 1, Supplementary Figures S1 and S2).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Tcl1 À/À mice develop alopecia and skin impairment: macroscopical and histopathological analysis Tcl1 À/À mice show no gross histological or physical abnormality at birth, except a fertility defect and a mild impairment of the immune system in adult life (Kang et al, 2005;Narducci et al, 1997aNarducci et al, , b, 2002. These mice develop a form of mild alopecia starting from the head and neck region (Figure 1, Supplementary Figures S1 and S2).…”
Section: Resultsmentioning
confidence: 99%
“…Here we show that CD34 þ cells are diminished in Tcl1 À/À mice. We do not know if and how Tcl1 regulates CD34 expression; however, it has already been reported that Tcl1 and CD34 are co-expressed in the lymphoid compartment in the very early stage of B-cell differentiation (pro-B cells) (Narducci et al, 2000), and that this compartment of pro-B cells is also less numerous in the Tcl1 À/À mice (Kang et al, 2005).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Bone marrow cells were prepared as described elsewhere (23). Bone marrow cells (1 ϫ 10 6 ) were labeled with CFSE (carboxyfluorescein diacetate, succinimidyl ester) (Molecular Probes, Eugene, OR) at a final concentration of 1 M, and CFSE was quenched by further incubation in serumcontaining medium and extensively washed in RPMI medium.…”
Section: Functional Characterization Of Gm-csf and Cd40l Incorporatedmentioning
confidence: 99%